2001
DOI: 10.1177/10597123010093004
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Based Navigational Strategies for Mobile Agents

Abstract: Although most species are sensitive to various chemicals, and olfactory skills such as search strategies for finding nutritious substance are seemingly simple, these basic skills are still not fully understood. Traditionally, chemotaxis has been considered as the fundamental chemosensory navigational mechanism for most species. Previous studies have demonstrated, however, that biased random walk is the more fundamental navigational strategy in various types of diffusion fields. Biased random walk is a robust a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Inspired by Berg and Brown's (1972) study, we introduced biased random walk strategies at a macroscopic scale for mobile robots and showed that BRW is a robust and yet more efficient strategy than chemotaxis in unstable and noisy chemical fields (Kadar and Virk, 1998a). In addition to locating the static point odour source in unstable chemical fields, BRW has also been assessed for moving targets (Kadar and Virk, 1998c), odour trails (Virk and Kadar, 2000) and turbulent plumes (Lytridis et al, 2001). In Virk et al's (1998) study, a fuzzy logicbased sensor fusion approach demonstrated that the BRW algorithm could be combined with obstacle avoidance based on other traditional distal sensors (acoustic, infrared, etc.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Inspired by Berg and Brown's (1972) study, we introduced biased random walk strategies at a macroscopic scale for mobile robots and showed that BRW is a robust and yet more efficient strategy than chemotaxis in unstable and noisy chemical fields (Kadar and Virk, 1998a). In addition to locating the static point odour source in unstable chemical fields, BRW has also been assessed for moving targets (Kadar and Virk, 1998c), odour trails (Virk and Kadar, 2000) and turbulent plumes (Lytridis et al, 2001). In Virk et al's (1998) study, a fuzzy logicbased sensor fusion approach demonstrated that the BRW algorithm could be combined with obstacle avoidance based on other traditional distal sensors (acoustic, infrared, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Biological studies have already demonstrated the use of various search methods (e.g., chemotaxis and biased random walk), but robotics research could provide new ways to investigate principles of olfactory-based search skills (Webb, 2000;Grasso, 2001). In previous studies on odour source localisation, we have tested three biologically inspired search strategies: chemotaxis, biased random walk, and a combination of these methods (Kadar and Virk, 1998;Lytridis et al, 2001). The main objective of the present paper is to demonstrate how simulation and robot experiments could be used conjointly to systematically study these search strategies.…”
mentioning
confidence: 98%
“…While previous studies have shown that wandering albatrosses forage over both oceanic (depths of 2,000 m or more) and neritic (depths of 2,000 m or less) zones by using both foraging-in-flight and sit-and-wait strategies (11), no study has ever detailed fine-scale movement of any procellariiform at sea with a view toward investigating the sensory basis of foraging, particularly with respect to odor tracking. How animals track odors in water and air is, however, a topic of considerable broader interest with respect to developing algorithms for plume-following behavior at various spatial scales (12,13).…”
mentioning
confidence: 99%
“…Leveraging multiple robots for distributed search has its own peculiarities, many of which have been explored during the last decade. Multirobot search algorithms proposed in the literature include biasing expansion swarm approaches [11], biased random walk [12], particle swarm optimization [13], gradient climbing techniques [14], infotaxis [15], probabilistic reasoning [16], search through exploration [17], physics-based swarming [18], attraction-repulsion swarming [19], and formation-based algorithms [20], [21].…”
Section: Introductionmentioning
confidence: 99%